Complex Systems Design & Management : Proceedings of the Tenth International Conference on Complex Systems Design and Management, CSD&M Paris 2019 /: Proceedings of the Tenth International Conference on Complex Systems Design and Management, CSD&M Paris 2019. ([2020]) - Unknown
No abstract available